Produção acadêmica brasileira em Contabilidade de Custos aplicada ao setor público: plataformas teórico-metodológicas e aspectos normativos - Nascimento, Cícero Philip Soares do (2013)
Cost accounting applied to the public sector presents great challenges before the advent of guidelines for the structuring of the information cost of the public sector system. Such regulatory guidelines, driven by Brazilian accounting standards applied to the public sector, enable improvements in information quality of information costs in the public sector. Meanwhile, on the potential changes of accounting applied to the public sector cost scenario, the questioning about the theoretical and methodological stage area arises, considering there is a need to expand the discussion about concepts and theoretical bases of change demanded by the context. In this scenario, the objective of this study is to examine the theoretical and methodological platforms Brazilian academic production accounting applied to the public sector costs, considering the regulatory aspects governing this issue. The study adopts a mixed approach, comprising the combination of qualitative elements in the collection by means of content analysis, and quantitative, as evidenced by descriptive statistics. This is a descriptive study, and documentary research as the main strategy used. We identified 21 programs Postgraduate stricto sensu the accounting field as depositary environment of intellectual products produced, especially theses and dissertations, as well as 18 journals that maintain a relationship with these programs analyzed in the period 2003-2013. Results show that only 47 papers deal of cost accounting applied to the public sector, while 295 deal with the accounting applied to private sector costs. Observed decline of scientific production from the late 2000s. Regard to theoretical platforms, there was little use of theoretical models that support research, signaling that the focus is not to predict or explain phenomena but describe them; great emphasis on the use of authors who treat of cost accounting in the private sector, with no development or dissemination of literature to a genuine area; and themes focused on hospital or university settings. As for the methodological platforms, it was found possessing qualitative, descriptive and exploratory approach; use strategies for the case study research, documentary and bibliographic research; adopt the document research, interview and questionnaire as the main data collection techniques; and analyze the data using descriptive statistics. As for the regulatory aspects of the Brazilian Standard Applied to the Public Sector Accounting - NBCT 16:11, it was observed that the value of cost information focuses on managerial purposes; the objective of an information system cost is focused on supporting the decision making processes; and Activity Based Costing is the main method of costing studied by academia. At the end, we concluded that the theoretical and methodological platforms Brazilian academic production cost accounting applied to the public sector develop with particular incipient and devoid of identity theoretical framework capable of portraying the phenomena observed in public organizations to the changes, besides the methodological approaches grounded in the phenomenological paradigm.